2021
DOI: 10.3389/fphar.2021.758830
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microsatellite Instability in Colorectal Cancer Patients With a Plasma-Based Real-Time PCR Analysis

Abstract: A microsatellite instability (MSI) test is crucial for screening for HNPCC (Hereditary nonpolyposis colorectal cancer; Lynch syndrome) and optimization of colorectal cancer (CRC) treatment. Mismatch repair (MMR) deficiency is a predictor for good response of immune checkpoint inhibitors in various malignancies. In this study, we evaluated the results of a newly developed plasma-based real-time PCR kit for the detection of MSI in CRC patients. We assessed a peptide nucleotide acid (PNA) probe-mediated real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Multiple fluorescence polymerase chain reaction capillary electrophoresis (PCR-CE) detection, PCR melting curve method, and next-generation sequencing (NGS) are employed to detect mutated microsatellite markers and categorize MSI status. 20,21 The most commonly used panel is the Bethesda panel, which includes two mononucleotides (BAT-25 and BAT-26) and three dinucleotide (D2S123, D5S346, and D17S250) repeats. 22 MSI status is categorized based on the number of mutated markers: MSI-H classification is assigned when two or more of the five markers exhibit instability, MSI-L when only one marker shows instability, and MSS when no markers display instability.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple fluorescence polymerase chain reaction capillary electrophoresis (PCR-CE) detection, PCR melting curve method, and next-generation sequencing (NGS) are employed to detect mutated microsatellite markers and categorize MSI status. 20,21 The most commonly used panel is the Bethesda panel, which includes two mononucleotides (BAT-25 and BAT-26) and three dinucleotide (D2S123, D5S346, and D17S250) repeats. 22 MSI status is categorized based on the number of mutated markers: MSI-H classification is assigned when two or more of the five markers exhibit instability, MSI-L when only one marker shows instability, and MSS when no markers display instability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated the application of deep learning to predict a patient's response to therapy and to predict biologically relevant information from morphological features extracted from standard histology slides. For example, microsatellite instability (MSI) is one of the key markers informing the treatment decision in colorectal cancer (CRC) [17,1]. Research has shown it is possible to predict MSI status using deep learning from standard hematoxylin and eosin (H&E) stained slide images [3,7,11].…”
Section: Introductionmentioning
confidence: 99%